Comparing the contribution of commercial and recreational marine fishing to regional economies in Europe. An Input-Output approach applied to Asturias (Northwest Spain). (August 2020) - García-de-la-Fuente, Laura; García-Flórez, Lucía; Fernández-Rueda, Mª Pino; Alcázar-Álvarez, Jorge; Colina-Vuelta, Arturo; Fernández-Vázquez, Esteban; Ramos-Carvajal, Carmen
Abstract: An Input-Output model was applied to quantify and compare, for the first time in Europe, the economic contribution of marine recreational (MRF) and commercial fishing (MCF) to a regional economy (Asturias, Spain). The approach considers separately the commercial artisanal fishing (MCAF) and attempts to overcome traditional problems concerning the treatment of recreational expenditure and the direct comparability between these marine activities. Although final consumption by households of fish and sea products from MCF was similar to the final consumption of resident recreational fishermen (MRF) in 2010, commercial fishing supported more gross value added (GVA) and jobs than recreational fishing. Multipliers of final consumption show that MRF had slightly higher potential than MCF to induce the final output of the regional economy, and both of them show a similar effect on GVA; nevertheless, the multiplier effect on employment is greater in the professional sector, especially in the artisanal fleets. MRF and MCF private consumption jointly supported 0.25% of the regional GVA and 0.40% of the employment in 2010; however, the economic effect of MRF expenditure remains strongly linked to retail, manufacturing and hotels/restaurants, while final consumption associated with MCF and MCAF supports the fishing industry itself and, to a much lesser extent, manufacturing. The article discusses the challenge of improving European economic information on MRF to be used in impact assessments for decision-making, as well as a future Data Collection Framework in which recreational expenditures and economic surveys are specifically designed to be applied in impact studies. Highlights: Connect Input-Output and data collection on recreational expenses to assess impact. Region with non-tourism recreational fisheries and high rate of local anglers. Higher gross contribution of marine commercial fishing to value added and jobs. Commercial artisanal fishing shows the highest multiplier effect on regional jobs. Different sectoral impacts of recreational and commercial fishing, complementary.